Avaliação da política de emprego para pessoa com deficiência no Município de Maracanaú-CE - Santos, Francisca Edinalda Lima (2011)
This study identified and evaluated the actions that strengthen the employment policy for persons with disabilities in the City of Maracanaú (CE). The study was quantitative research, as well as qualitative data that supported us in understanding the subjectivity of our subjects. The analysis method used was the Case Study. With the literature we obtained further studies, which allowed a parallel increase in the analysis. The fieldwork took place in the town of Marazion. The sample consisted of 127 persons with disabilities, and of these, 23 were families of disabled where we collect the data, 02 interviews with the psychologists of the Department of Human Resources for two companies and 01 technical SINE / IDT 01 and Technical Supervision Regional Labor. The survey of data from the subjects took place from March to August 2010. For the data collection was a questionnaire, interviews were conducted and also used a field diary. The research subjects were people with disabilities who are in and out of the labor market, families, professionals who provide services in public agencies and staffing companies. In the first part of the work has a historical approach of the different civilizations, drawing on authors as Bianchetti (1988), Skiliar (1997) and Cavalcante (2001). To reflect on people with disabilities and work with the concepts of prejudice, exclusion and stigma, the grounds was built with the study of authors such as Goffman (1988) and Sassaki (2006). To address issues pertaining to the work and its importance in human occupation from the perspective of people with disabilities, the theoretical basis was given to authors such as Schruber (2002) and Wagon (2004). To conclude the theoretical strands, worked as issues of citizenship and public policy from the perspective of social inclusion and legal support for people with disabilities, where we sought to authors such as Silva (2000) and Behring and Boschetti (2006) for dialogue. We conclude that, despite the presence of the barrier of prejudice and lack of knowledge and skill about the potentials of the disabled person, it is possible to prove, as was demonstrated in the experience of the project Apprentice, his capacity for labor market. This project forms an individual more productive, strengthening the fight to include these subjects in every sense of your life.